Implementation and Operational Research: Programmatic Feasibility of Dried Blood Spots for the Virological Follow-up of Patients on Antiretroviral Treatment in Nord Kivu, Democratic Republic of the Congo. (1st January 2016) - Boillot, François; Serrano, Laetitia; Muwonga, Jeremie; Kabuayi, Jean Pierre; Kambale, Alain; Mutaka, Fidèle; Fujiwara, Paula I.; Decosas, Josef; Peeters, Martine; Delaporte, Eric
Abstract : Background: As part of its policy to shift monitoring of antiretroviral therapy (ART) to primary health care (PHC) workers, the Ministry of Health of the Democratic Republic of Congo (DRC) tested the feasibility of using dried blood spots (DBS) for viral load (VL) quantification and genotypic drug resistance testing in off-site high-throughput laboratories. Methods: DBS samples from adults on ART were collected in 13 decentralized PHC facilities in the Nord-Kivu province and shipped during program quarterly supervision to a reference laboratory 2000 km away, where VL was quantified with a commercial assay (m2000rt, Abbott). A second DBS was sent to a World Health Organization (WHO)-accredited laboratory for repeat VL quantification on a subset of samples with a generic assay (Biocentric) and genotypic drug resistance testing when VL >1000 copies per milliliter. Findings: Constraints arose because of an interruption in national laboratory funding rather than to technical or logistic problems. All samples were assessed by both VL assays to allow ART adjustment. Median DBS turnaround time was 37 days (interquartile range: 9–59). Assays performed unequally with DBS, impacting clinical decisions, quality assurance, and overall cost-effectiveness. Based on m2000rt or generic assay, 31.3% of patients were on virological failure (VF) and 14.8% presented resistance mutations versus 50.3% and 15.4%, respectively. Conclusion: This study confirms that current technologies involving DBS make virological monitoring of ART possible at PHC level, including in challenging environments, provided organizational issues are addressed. Adequate core funding of HIV laboratories and adapted choice of VL assays require urgent attention to control resistance to ART as coverage expands. Abstract : Supplemental Digital Content is Available in the Text.